2004
DOI: 10.1128/aem.70.7.4267-4275.2004
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Bacterial Populations in Dairy Wastewaters by Use of 16S rRNA Gene Sequences and Other Genetic Markers

Abstract: Hydraulic flush waste removal systems coupled to solid/liquid separators and circulated treatment lagoons are commonly utilized to manage the large amounts of animal waste produced on high-intensity dairy farms. Although these systems are common, little is known about the microbial populations that inhabit them or how they change as they traverse the system. Using culture-based and non-culture-based methods, we characterized the microbial community structure of manure, water from the separator pit, and water f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 57 publications
1
46
0
Order By: Relevance
“…They were not affiliated with Clostridium species commonly associated with silage and defective cheese (24) but rather with C. lituseburense. This species was previously found to be predominant in cow manure and dairy wastewaters, along with Turicibacter sanguinis (29). In addition, Ralstonia sp.…”
Section: Discussionmentioning
confidence: 97%
“…They were not affiliated with Clostridium species commonly associated with silage and defective cheese (24) but rather with C. lituseburense. This species was previously found to be predominant in cow manure and dairy wastewaters, along with Turicibacter sanguinis (29). In addition, Ralstonia sp.…”
Section: Discussionmentioning
confidence: 97%
“…Three sequences from porcine GI tracts that were communicated prior to the description of the species are highly homologous to Turicibacter (27). Turicibacter has also been reported from insect hindguts, dairy wastewaters, and raw milk (8,9,34). However, as only one species has been cultured (3), the physiological diversity of the members of this genus is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The material in these tanks, as in the effluent storage tanks for the aerobic and anaerobic reactors, received no mixing except when samples were taken and was maintained at room temperature for the duration of the experiment. Previous studies in our laboratory have shown that both aerobic and anaerobic treatments of manure reduce microbial diversity and chemical variability (26); thus, a sampling scheme was developed on the hypothesis that the feed material would have the most microbial and chemical variability. Therefore, the feed material was assayed weekly as described below when fresh material was added.…”
Section: Methodsmentioning
confidence: 99%